CLIMATIC CHANGE AND PESTICIDES USAGE: A BRIEF REVIEW OF THEIR IMPLICATIVE RELATIONSHIP - Ukhurebor, K E; Aigbe, U O; Olayinka, A S; Nwankwo, W; Emegha, J O (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2020)
Pesticides are very important for the prevention, mitigation, destruction of pests and diseases for the improvement of agricultural efficiency due to their contributions to agricultural yields and improving the standard of living. Considering the dynamicity and influence of weather in our everyday lives, it is obvious that the effects of pesticides might also be a contributing factor and vice versa. Climate change could have an influence on both pesticides’ usage, as well as the losses of pesticides to the environment. Presently, the issue of climate change is one of the furthermost intellectual challenging issues facing the entire human race. Therefore, we must continue to protect our environment from these unfavorable effects of climate change by extremely dipping the emissions of greenhouse gases especially via the use of chemical substances such as pesticides. In this review study, we will briefly attempt to give an insight and try to bridge the uncertainty surrounding the effects of the use of pesticides and its relationship to climate change effects on the environment.